Aspects of User Intellectual Property Rights Ownership in Blockchain-Based Online Game Platform Blankos Block Party - Maulana, Muhammad Asrul; Isthikomah; Amalina, Zaskiya; Putri, Mega Oktaviana; Bimantara, Arya (Westscience Press, 2025)
This research focuses on the legal relationship between users and platform owners in Blankos Block Party's blockchain-based online gaming platform, regarding copyright ownership. In addition, this research aims to understand the rights and obligations of the parties in determining asset protection and the benefits that can be obtained. This research uses normative method with statute approach and conceptual approach. The results of this study found that the platform owner has exclusive ownership rights to the material in the software and can regulate the use of user content. Users have the right to use the software and ownership of the content they produce, but are also obliged to comply with the terms of use and maintain the validity of the content. Platform owners are responsible for protecting users' intellectual property rights, while users are responsible for uploaded content and must secure the necessary rights or permissions.